Topos, Text, and the Parody Problem in Bach's Mass in B minor, BWV 232 - Szeker-Madden, Lisa (Canadian University Music Review / Revue de musique des universités canadiennes)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 1995)
Even though parody and borrowing have long been recognized as legitimate features of Bach's compositional practices, the criteria by which the composer selected appropriate material to parody remains problematic. Christoph Wolff and Güther Stiller, for example, suggest that musical elements, such as the quality of the original or its potential for further embellishment, represent possible criteria. On the other hand, textual elements such as analogous subjects, "affects," and metrical patterns between old and new texts also many have factored into Bach's criteria. In an effort to redress the imposition of these twentieth-century solutions to what is in effect an eighteenth-century phenomenon, this study undertakes a cultural/contextual examination of the Crucifixus movement from the Mass in B minor and its model, the opening chorus of Cantata 12. Indeed, a logical analysis of both texts reveals that an equivalence of topoi, or topics, represents an important criterion in the selection of an appropriate model from which to borrow. Moreover, a musical-rhetorical analysis confirms that Bach's borrowings from the opening chorus of Cantata 12 are actually musical-rhetorical figures. His application of the parody procedure thus represents the re-use of specific musical-rhetorical gestures which are suitable for the embellishment of a particular topos.